Fatigue Analysis of Random Vibration for Converter Cabinet - DING Jie; TANG Yutu (Kongzhi Yu Xinxi Jishu)
Vibration fatigue of structure easily arises due to the dynamie load, so that frequency domain fatigue analysis technique is used to involve dynamic properties of the structure. Taking a converter cabinet as a research object, the transfer functions between input and structural stress are obtained by frequency response analysis. The fatigue life is predicted in frequency domain according to the results of frequency response analysis on the finite element of the converter’s cabinet and the ASD(Acceleration Spectral Density) spectrum from the standard GB/T 21563-2008 Railway applications- Rolling stock equipment- Shock and vibration tests. Failures of the converter cabinet in vibration test are successfully analyzed with simulation and the correctness of simulated results is verified.